Fundamental Principles of Risk Management in Restructuring, Reorganization, and Liquidation of Non-Profit and Profit-Oriented Companies - Deni Sunaryo; Dhany Isnaeni Darmawan; Anisya Dwi Wulandari Kaya; Melynda Anggraini; Melda Dwi Rahma (International Journal of Management Research and Economics, 2025)
The implementation of financial risk management policies and principles is a critical aspect of managing the banking sector, non-profit organizations, and business environments in Indonesia. The adoption of International Financial Reporting Standards (IFRS) has significantly altered accounting practices in Indonesia, yielding both opportunities and challenges for companies. Furthermore, credit restructuring, encapsulated in the "3R" principle, has emerged as a strategic solution to address non-performing loans, particularly during the COVID-19 pandemic, as regulated in POJK 11/POJK.03/2020.In the legal domain, corporate reorganization is increasingly recognized as a vital strategy to prevent bankruptcy, emphasizing the need for more comprehensive and transparent legal frameworks. In the Islamic banking sector, liquidity risk management is paramount to ensure economic stability and maintain public trust. Meanwhile, non-profit organizations, such as AIESEC Indonesia, face distinct challenges in implementing effective internal control systems, with a focus on enhancing financial transparency and accountability.This article also highlights the importance of organizational change management as a driver of operational efficiency and adaptability to external challenges. Employing a descriptive and normative approach, it explores the intersection of economic policies, legal frameworks, and management practices in addressing the complexities of globalization, economic crises, and efficiency demands.In conclusion, sustainable practices in risk management, legal adaptation, and internal system strengthening are pivotal to achieving resilience and success across financial and organizational sectors.